The Idea of Transfiguration in the Early German Reception of Mozart’s Requiem - Kramer, Elizabeth (Current Musicology, 2006)
Over the past two hundred years, authorship disputes have dominated scholarly discussions about Mozart’s Requiem. From the analysis of handwriting to the provenance of manuscript evidence, much debate has occurred over who wrote what when and about the relationship of these details to the larger contexts for the work. l In our attempts to present new evidence and theories regarding the Requiem, however, we have largely ignored the very reasons for investigating its genesis and composition in the first place. Our motivations as scholars, given Mozart’s canonical status and the continual influence of the work, may seem obvious today. But what inspired the initial conversation? This essay works from the premise that early nineteenth-century interest in the authorship of the Requiem grew out of a wider movement of Kunstreligion (art religion) in German musical aesthetics of the time. In connection with Kunstreligion, the idea of transfiguration entered music criticism and writings on aesthetics around 1800 and played a pivotal role in early texts about the Requiem. Initially employed in vivid comparisons of the Requiem to Raphael’s Transfiguration of Christ, the idea of transfiguration shaped the debates about the authenticity of Mozart’s composition in the 1820s. Critics such as Friedrich Rochlitz, E. T. A. Hoffmann, Gottfried Weber, and Adolf Bernhard Marx understood the Requiem as the transfiguration of its composer, listeners, and of music itself. The composition was imagined to be a site of Mozart’s own transfiguration, and concert reviewers described the heightened “spiritual listening” of some of the Requiem’s first performers and audiences, whose profound experiences were seemingly evoked by presentations of the work. Drawing on a slightly different sense of the idea of transfiguration, the Requiem itself was at the center of a transformation of existing generic categories: what previously would have been considered “church music” (“Kirchenmusik”) now fit into a newer category of “religious music” (“religiose Musik”). These manifestations of transfiguration, which developed out of the broader movement of early nineteenth-century Kunstreligion, led commentators to express concerns about the authenticity of Mozart’s final work. After a survey of the ideas of Kunstreligion and transfiguration in early nineteenth-century writings about music, this essay traces the role of the concept of transfiguration in the reception of the Requiem, from the early anecdotes to the later controversy.